The Ceremonial City : Toulouse Observed, 1738-1780 - Schneider, Robert A. (Book collections on Project MUSE., 2001)
From public executions to religious processions to political festivities, Toulouse's ceremonial life was remarkably rich in the decades prior to the French Revolution. In an engaging portrait that conveys this provincial city in all its splendor and misery, Robert Schneider explores how Toulouse's civic and community life was represented in the stagings of various ceremonies. His inquiry is based on the unpublished diaries of Pierre Barthes, a Latin tutor who was both a devout Catholic and a monarchist, and who recorded forty years of public activity in ways that reflected the mounting social.